Re-examining and Redeeming the Tragic Queen: Euripides’ "Hecuba" in Two Versions by Frank McGuinness (2004) and Marina Carr (2015) - González Chacón, María del Mar (Complutense Journal of English Studies, 2017)
A common approach to Irish theatre during the last years has been the identification of the interest by the playwrights in rewriting, adapting or translating Greek tragedies. This article examines Euripides’ Hecuba by Frank McGuinness (2004) and Marina Carr (2015) from a comparative approach and emphasizes the revision and redemption of the figure of the queen of Troy in the hands of both Irish contemporary playwrights. From this perspective, a new image of Hecuba is suggested which adds to the classical heroine modern traits that allow to parallel her story with Ireland’s (hi)stories of war as well as to redeem her from the burden of the myth which is then unmasked. The analysis of Hecuba’s speeches in the three versions reveals language and plot variations that have allowed the myth to continue traveling in time.